2002
DOI: 10.1016/s0925-4439(02)00168-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced augmentation of annexin IV in cultured cells and the enhancement of cytotoxicity by overexpression of annexin IV by ethanol

Abstract: The annexins are a family of highly homologous Ca(2+) and phospholipid binding proteins. The expressive amounts of several annexins have been shown to alter in certain pathological states such as brain ischemia and Alzheimer's disease. It has been demonstrated that ethanol induces cytotoxicity, which results in brain damage. In this study, we examined the relationship between ethanol-induced cytotoxicity and the intrinsic amount of annexins using cell lines (rat glioma C6 cells and human adenocarcinoma A549 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…By western blotting analysis, Sohma et al showed significantly increased expression of annexin A4 in the hippocampi of postmortem brains of alcoholic patients compared with controls [69]. In addition to this finding, the augmentation of annexin A4 expression following ethanol exposure was also demonstrated in cultured cells (rat glioma C6 cells and human adenocarcinoma A549 cells), suggesting that the expression of annexin A4 is induced by specific cellular stress [70].…”
Section: Functions Of Annexin A4 and Relevance To Cancermentioning
confidence: 91%
“…By western blotting analysis, Sohma et al showed significantly increased expression of annexin A4 in the hippocampi of postmortem brains of alcoholic patients compared with controls [69]. In addition to this finding, the augmentation of annexin A4 expression following ethanol exposure was also demonstrated in cultured cells (rat glioma C6 cells and human adenocarcinoma A549 cells), suggesting that the expression of annexin A4 is induced by specific cellular stress [70].…”
Section: Functions Of Annexin A4 and Relevance To Cancermentioning
confidence: 91%
“…The p50-p65 heterodimers are sequestered in the cytoplasm through interactions with Ij-B in the resting state. Following application of various stimuli, these dimers are released from Ij-B and translocate to the nucleus, where they activate the transcription of various downstream target genes [12][13][14][15][16][17][18][19]. To determine the effects of ANXA4 on the composition of the NF-jB complex, we performed immunoprecipitation experiments using extracts from control or ANXA4-overexpressing Bosc 23 cells.…”
Section: Anxa4 Interacts With the P50 Subunit Of Nf-jbmentioning
confidence: 99%
“…NF-jB, one of the most extensively characterized transcription factors in mammalian cells, regulates numerous genes involved in the immune response, cell proliferation, differentiation, survival, and apoptosis [12][13][14][15][16]. The NF-jB family is composed of five members, specifically, p65 (RelA), p105/p50 (NF-jB1), p100/p52 (NF-jB2), c-Rel, and RelB [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Short-term exposure attenuates the channel activity; however, long-term exposure up regulates the number of channels, which in turn increases the intracellular Ca 2 ϩ -concentration. Using neuronal and glial cell cultures, increased expression of annexin IV, a calcium and phospholipid binding protein, has been found in relation to heavy ethanol exposure (Ohkawa et al 2002) and annexin IV may be a specifi c marker for the effects of ethanol. The augmented expression of annexin IV in specimens from alcoholics suggests that it may be involved in the recovery from the damage caused by alcohol.…”
Section: Othersmentioning
confidence: 99%